2012
DOI: 10.5194/acp-12-5147-2012
|View full text |Cite
|
Sign up to set email alerts
|

Dust resuspension under weak wind conditions: direct observations and model

Abstract: Abstract. The results of direct observations of fine mineral dust aerosol (0.15-15 µm) were carried out on extensive sand areas in desertificated lands of Kalmykia in 2007Kalmykia in , 2009Kalmykia in , and 2010 under conditions of weak wind and strong heating of the surface, almost in the absence of saltation processes. These results show that the fine mineral dust aerosol (0.15-0.5 µm) in the region under consideration contributes considerably to the total aerosol content of the atmospheric surface layer.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 32 publications
(34 reference statements)
1
13
0
1
Order By: Relevance
“…It is worth mentioning that weak wind conditions can also be responsible for a high contribution of fine (0.15-15µm) mineral dust fraction in the total aerosol content (Golitsyn et al, 1997;Golitsyn et al, 2003;Chkhetiani et al, 2012), being also observed in Beijing during the winter haze episodes (Yang et al, 2017;Yang et al, 2018) where negative Δ 33 S-values primarily occur (Han et al, 2017). Although the contribution of sulfates from terrigeneous sources has been estimated to a maximal value of 3.84 ± 4.40 to 5.62 ± 6.52% deduced from Ca² + concentration (Han et al, 2017).…”
Section: Photooxidation Of So2 In Presence Of Mineral Dustmentioning
confidence: 99%
“…It is worth mentioning that weak wind conditions can also be responsible for a high contribution of fine (0.15-15µm) mineral dust fraction in the total aerosol content (Golitsyn et al, 1997;Golitsyn et al, 2003;Chkhetiani et al, 2012), being also observed in Beijing during the winter haze episodes (Yang et al, 2017;Yang et al, 2018) where negative Δ 33 S-values primarily occur (Han et al, 2017). Although the contribution of sulfates from terrigeneous sources has been estimated to a maximal value of 3.84 ± 4.40 to 5.62 ± 6.52% deduced from Ca² + concentration (Han et al, 2017).…”
Section: Photooxidation Of So2 In Presence Of Mineral Dustmentioning
confidence: 99%
“…Recently, effort has been made to investigate the process of Convective Turbulent Dust Emission (CTDE), the most important form of aerodynamic dust entrainment [ Klose and Shao , ]. Field experiments have been carried out to investigate CTDE among other processes [e.g., Heintzenberg , ; Chkhetiani et al , ]. Ansmann et al [] analyzed the vertical profiles of convective dust plumes by use of lidar measurements of the Saharan Mineral Dust Experiment (SAMUM) in Morocco and suggested that convective processes play an important role in dust production, particularly at low mean wind speeds (< 7 ms −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…While strong dust events are important to episodic increases in atmospheric dust concentration, CTDE is arguably more important in maintaining the background dust concentration and the continuous dust supply to the ocean to sustain the ocean biomass productivity [ Klose and Shao , ]. Thus, CTDE contributes to global dust variability mainly on seasonal, annual, or longer time scales [ Chkhetiani et al ., ]. The importance of CTDE is however yet to be fully quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Dust emission without saltation has been observed in field and wind tunnel experiments [ Gillette and Sinclair , ; Shao et al ., ; Gillette et al ., , ; Loosmore and Hunt , ; Golitsyn et al ., ; Chkhetiani et al ., ]. Most of the field experiments on CTDE are carried out in desert regions [e.g., Gillette and Sinclair , ; Gillette et al ., ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation